Peristiwa Literasi dalam Novel "Di Tanah Lada" Karya Ziggy Zezsyazeoviennazabrizkie dan "Merakit Kapal" Karya Shion Miura - Ahmad Abdul Karim; Dian Hartati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The purpose of this study is to describe literacy events in the novels "Di Tanah Lada" by Ziggy Zezsyazeoviennazabrizkie and "Merakit Kapal" by Shion Miura. This study uses a qualitative approach and a text study method that relies on comparative literature studies by combining literary and anthropological theories. The study approach and design were used to examine the depiction of literacy events developed by Indonesian and Japanese authors. The data collection technique used literature study, listening, reading, and taking notes on two novels' narration, dialogue, or monologue. The collected data is then processed by data analysis, including data selection, data explanation through an in-depth understanding of meaning, observation, and exploration of two literary texts' message (content), and drawing conclusions. The results of the analysis show that: in Indonesian novels, children read books, while in Japanese novels, adults read books; child characters in Indonesian novels communicate in standard language and adults in Japanese novels communicate in standard language; In Indonesian novels, dictionaries are used as guidelines for understanding language by children's characters, while in Japanese novels adults struggle to compile dictionaries.